AgO-decorated multi-dimensional chrysanthemum-like NiCo2O4 mounted on nickel foam as a highly efficient and stable electrocatalyst for the oxygen evolution reaction. Issue 13 (20th March 2020) - Wang, Lei; Wang, Jianzhi; Wang, Miao; Li, Pan; Tong, Jing; Yu, Faquan
Abstract : The highly hierarchical mesoporous structure of NiCo2 O4 /AgO bestowed the high surface area and AgO upgraded the ratio of Co 3+ /Co 2+ . Abstract : AgO nanoparticles were successfully integrated into NiCo2 O4 nanosheets for enhanced electrochemical catalysis ability and stability in the oxygen evolution reaction (OER). The chrysanthemum-like NiCo2 O4 /AgO composites mounted on nickel foam (NF) were synthesized by a hydrothermal–calcination method. AgO upgraded the ratio of Co 3+ /Co 2+ and thus regulated the intrinsic activity of the species. The highly hierarchical structure of NiCo2 O4 /AgO composed of 0D AgO nanoparticles, 1D NiCo2 O4 needles, 2D NiCo2 O4 nanosheets, and 3D chrysanthemum-like bundles grown on NF bestowed the high surface area and mesoporous structure for the easy evolution of O2 . The Ni atoms in NiCo2 O4 originating in situ from NF in the process of AgO formation produced an integrated electrode of the active component of NiCo2 O4 bound on NF with a superb highway for charge transfer. AgO significantly tuned the structure and physicochemical properties of NiCo2 O4 . As a result, NiCo2 O4 /AgO/NF exhibited excellent OER performance with an overpotential of 232 mV to obtain a current density of 10 mAcm −2 in an alkaline electrolyte, and the catalyst showed a small loss of the initial catalyst activity for 50 h and over 5000 cycles. This study provides a pathway for developing high-performance OER electrocatalysts.